A qualitative stakeholder analysis of avian influenza policy in Bangladesh - Chattopadhyay, Kaushik; Fournié, Guillaume; Kalam, Md. Abdul; Biswas, Paritosh K.; Hoque, Ahasanul; Debnath, Nitish C.; Rahman, Mahmudur; Pfeiffer, Dirk U.; Harper, David; Heymann, David L. (Springer, 2017)
Avian influenza is a major animal and public health concern in Bangladesh. A decade after development and implementation of the first national avian influenza and human pandemic influenza preparedness and response plan in Bangladesh, a two-stage qualitative stakeholder analysis was performed in relation to the policy development process and the actual policy. This study specifically aimed to identify the future policy options to prevent and control avian influenza and other poultry-related zoonotic diseases in Bangladesh. It was recommended that the policy should be based on the One Health concept, be evidence-based, sustainable, reviewed and updated as necessary. The future policy environment that is suitable for developing and implementing these policies should take into account the following points: the need to formally engage multiple sectors, the need for clear and acceptable leadership, roles and responsibilities, and the need for a common pool of resources and provision for transferring resources. Most of these recommendations are directed towards the Government of Bangladesh. However, other sectors, including research and poultry production stakeholders, also have a major role to play to inform policy-making and actively participate in the multi-sectoral approach.